No association of tobacco use and disease activity in multiple sclerosis. Issue 4 (August 2016) - Kvistad, Silje; Myhr, Kjell-Morten; Holmøy, Trygve; Benth, Jūratė Šaltytė; Løken-Amsrud, Kristin I.; Wergeland, Stig; Beiske, Antonie G.; Bjerve, Kristian S.; Hovdal, Harald; Lilleås, Finn; Midgard, Rune; Pedersen, Tom; et al.
Abstract : Objective: To study whether tobacco use is associated with MRI and clinical disease activity in patients with multiple sclerosis (MS). Methods: Prospective cohort study of 87 patients with relapsing-remitting MS originally included in a randomized placebo-controlled trial of omega-3 fatty acids in MS (the OFAMS Study). Serum levels of cotinine (biomarker of tobacco use) were analyzed at baseline and every 6 months for 2 years. MRI activity was assessed at baseline and monthly for 9 months and after 12 and 24 months. Results: Fifty-three patients (61%) had serum cotinine levels ≥85 nmol/L on ≥60% of the measurements and were considered tobacco users and 34 (39%) had cotinine levels <85 nmol/L, consistent with non–tobacco use. There was no association between tobacco use and the occurrence of new gadolinium-enhancing T1 lesions, new or enlarging T2 lesions, or their aggregate (combined unique activity). Furthermore, there was no association between cotinine levels and MRI activity for the tobacco users, and tobacco users did not have more relapses or Expanded Disability Status Scale progression. Conclusion: Our results indicate that tobacco use does not directly influence MRI activity or relapse rate in MS. This may implicate that the reported association between smoking and MS disease progression could be mediated through other mechanisms.